A Dual‐Responsive Platform Based on Antifouling Dendrimer–CuS Nanohybrids for Enhanced Tumor Delivery and Combination Therapy. Issue 6 (14th April 2021) - Xiong, Zhijuan; Wang, Yue; Zhu, Wei; Ouyang, Zhijun; Zhu, Yu; Shen, Mingwu; Xia, Jindong; Shi, Xiangyang
Abstract: Design of stimuli‐responsive nanomedicine with enhanced tumor delivery for combination therapy still remains a great challenge. Here, a unique design of an antifouling‐dendrimer‐based nanoplatform with dual pH‐ and redox‐responsiveness is reported to meet this challenge. First, generation 5 (G5) poly(amidoamine) dendrimers are modified with targeting ligand cyclic arginine–glycine–aspartic acid (RGD) peptide through a polyethylene glycol (PEG) spacer and zwitterion of thiolated N, N ‐dimethyl‐cysteamine‐carboxybetaine (CBT) via pH‐responsive benzoicimine bond to form G5.NH2 PEGRGDCBT conjugates. Then, doxorubicin (DOX) is linked to the functional G5 dendrimers through a redox‐responsive disulfide bond, followed by entrapment of CuS nanoparticles within the dendrimers. The created functional dendrimer–CuS nanohybrids with a CuS core size of 3.6 nm display a good antifouling property and excellent photothermal conversion property in the second near‐infrared window. In addition, the neutral surface charge of the nanohybrids is able to be switched to be positive in the tumor region with slightly acidic microenvironment due to the break of benzoicimine bond to promote their intracellular uptake, while the redox‐sensitive disulfide bond affords the fast release of the conjugated DOX within tumor cells to exert its therapeutic effect. Taken together with the CuS cores, the created dendrimer–CuS nanohybrids enable enhanced combination chemotherapy and photothermal therapy of tumors. Abstract : A unique design of an antifouling‐dendrimer‐based nanoplatform with dual pH‐ and redox‐responsiveness beneficial for enhanced tumor delivery is reported. The created dendrimer–CuS nanohybrids with a CuS core size of 3.6 nm have a second near‐infrared absorption feature, targeting specificity, and the ability to overcome different barriers of nanomedicine for enhanced tumor delivery, thus enabling excellent combination chemotherapy and photothermal therapy of tumors.